Sahih Al Bukhari: being the traditions of saying and doings of the prophet Muhammad AS narrated by his companions - Abi Abdullah Muhammad bin Ismail Al Bukhari (Dar el Fiker, 1993)
ir/vol.1,c.1-2; vol.2,c.1-2; vol.3,c.1-2; vol.4,c.1-2; vol.5,c.1-2; vol.6,c.1-2; vol.7,c.1-2; vol.8,c.1-2; vol.9,c.1-2/oen, Vol.5=C.3-4